An Ordinance Relating to Offenses and Disorderly Conduct, Olympia City Council, Ordinance No. 152, § 2 (Washington, 1882). - (:unkn) unknown (My University, 1882)
That any persons who shall draw exhibit or attempt to use any deadly weapon within the corporate limits of the City of Olympia, upon, to or against another person, shall be liable to a fine of not more than fifty nor less than twenty-five dollars.
Keywords: BRANDISHING